Surasem Aneka Rasa Untuk Penurun Diabetes dan Hipertensi - Fauzi, Gufron; Susanto, Hengky; Fauzan, Ahmad; Suharso, Wiwik (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Rice is the basic food of most Indonesian people. Currently available in three types of rice is white rice, brown rice, and embryo rice. Embryo rice is brown or red rice reprocessed to eliminate the phytic acid that are anti-nutrients in the hard layer of the epidermis and maintain embryo containing 66% of the total nutrition of rice.Embryo rice milk (surasem) uses the basic ingredients of embryonic red rice and mineral water at a dose of about 1 in 20, cooked within 46 minutes using a pressure cooker to decompose rice nutrients into the water. Subsequent processing is mixing surasem with the natural flavors of fresh fruits such as apples and berries, stirred and packed with a volume of 220 ml. Surasem excellent consumption by people with diabetics mellitus and hypertension due to low glucose and high anti oxidant content. This activity produces surasem with various fruit flavors in packs ready for sale, is distributed to the campus cafeteria and government agencies, and health care communities in Jember. Business development is done by increase production capacity, packaging design, marketing by leveraging information and communication technologies, and franchise business models based small and medium enterprises (UKM) to become a profitable business opportunity, contributing to improving the health and prosperity of society. Keywords : Embryo Rice, Natural flavorings, Surasem